INTEGRATED SCIENCE DIGITAL MODULE BASED ON SCIENTIFIC LITERACY: ANALYZING TECHNOLOGICAL CONTENT KNOWLEDGE (TCK) SKILLS IN INDUSTRY REVOLUTION 4.0 ERA - Hayati, Muriani Nur (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
The Industrial revolution 4.0 era has changed the view of educational model focus, where the old literacy knowledge (reading, writing, and mathematic) is not enough to be modal in a society. Curriculum reorientation is needed as new literacy so it keeps to be existed in that era. This research aims to understand validity and reading level of Integrated Sciences digital module based on scientific literacy students, and to analyze TCK skills of students after using digital module. This research use R & D method with subject of 44 science teacher candidate. Validating was done by expert validator. Reading level uses the result of scale test. TCK analyzed with descriptive percentage. Research showed there is acceptance using of Integrated Sciences digital module with reading level in intermediate level (51,90%) and validity is high (81,25%). TCK was analyzed with likert type scale in a enough criteria due to use of digital module. It is concluded that Integrated Science digital module based on scientific literacy can be used as learning module. Development of other digital module needs supporting from high institution so that it can hold on industry revolution 4.0 era.